Musculoskeletal Progenitor/Stromal Cell-Derived Mitochondria Modulate Cell Differentiation and Therapeutical Function - Jorgensen, Christian; Khoury, Maroun (Frontiers in Immunology, 2021)
Musculoskeletal stromal cells’ (MSC) metabolism impact cell differentiation as well as immune function. BM-MSCs show a preference for glycolysis during proliferation but shift to a more oxidative phosphorylation (OxPhos)-dependent metabolism during osteogenic and adipogenic differentiation. The MSC immunoregulatory function is achieved through rapid cell polarization and sustained production of immunoregulatory factors (including PGE2, HGF, IL1RA, IL6, IL8, IDO activity) in response to inflammatory stimuli, which requires cellular plasticity and adapted energetic metabolism. MSC immunomodulatory property requires a metabolic rewiring toward aerobic glycolysis to sustain the immune secretome. This can be achieved via hypoxia, pretreatment with small molecule-metabolic mediators such as oligomycin, or AKT/mTOR pathway modulation. Immunoregulatory effect of MSC on macrophages polarization and Th17 switch is related to the glycolytic status of the MSC. Indeed, MSC pre-treated with oligomycin decreased the M1/M2 ratio, inhibited T-CD4 proliferation and Th17 switch. Mitochondrial activity also impacts MSC metabolism. In their native environment, MSCs are present in a quiescent, low proliferation and high multi-potentiality state. hey appear to be primarily glycolytic, with active mitochondria (MT). However,MSC expansion induces a metabolic shift toward OXPhos, coupled with a higher MT activity. This shift is associated with an increased coupling between glycolysis and TCA cycle and a significantly increased production of ROS and dysfunctional mitochondria. In contrast, when MSC underwent differentiation, they showed a decreased capacity for the pentose phosphate pathway (PPP) and glycolysis, while the mitochondrial enzyme activities increased, indicating an augmented capacity for oxidative phosphorylation and beta-oxidation. MSCs respond to damaged or inflammed tissue through the transfer of MT to injured and immune cells, conveying a type of signaling that contributes to the restoration of cell homeostasis and immune function. The delivery of MT into injured cells increased ATP levels which in turn maintained cellular bioenergetics and recovered cell functions. MSC-derived MT may be transferred via tunelling nanotubes to undifferentiated cardiomyocytes and leading to maturation. In this review, we decipher the pathways and the mechanisms responsible for mitochondria transfer and activity. The eventual reversal of the metabolic and pro-inflammatory profile induced by the MT transfer, will open new avenues for the control of inflammatory diseases.